2013
DOI: 10.3892/ijo.2013.1773
|View full text |Cite
|
Sign up to set email alerts
|

The VHL tumor suppressor protein regulates tumorigenicity of U87-derived glioma stem-like cells by inhibiting the JAK/STAT signaling pathway

Abstract: The signal transducer and activator of transcription 3 (STAT3) factor plays an important role in the tumorigenicity of cancer stem cells. The purpose of this study was to investigate the inhibitory mechanism of this pathway acting through the tumor suppressor von Hippel-Lindau (VHL) protein in glioma cancer stem cells. We isolated floating neurosphere-forming CD133+ cells as glioma stem-like cells (GSLCs) by the MACS method. Furthermore, we examined these cells for their growth rate, ability to form colonies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…We then further confirmed the target of miR-566. VHL was shown to be involved in the tumorigenesis of glioma [9,21], and we found that the 3’ UTR of VHL contained 2 potential complimentary binding sites for miR-566. To validate this, we performed luciferase reporter assays using 3’ UTR sequence fragments of the VHL transcript containing the two predicted binding sites for miR-566 (Figure 3A).…”
Section: Resultsmentioning
confidence: 95%
“…We then further confirmed the target of miR-566. VHL was shown to be involved in the tumorigenesis of glioma [9,21], and we found that the 3’ UTR of VHL contained 2 potential complimentary binding sites for miR-566. To validate this, we performed luciferase reporter assays using 3’ UTR sequence fragments of the VHL transcript containing the two predicted binding sites for miR-566 (Figure 3A).…”
Section: Resultsmentioning
confidence: 95%
“…Studies now support retroversion of differentiated cells to a more stem-like or progenitor state, a change recently suggested to occur spontaneously in some cases, or to be induced or potentiated by TMZ therapy and possibly other cellular stressors including hypoxia and radiation [19]. HIF2α, loss of PTEN, and loss of von Hippel-Lindau have all been proposed as inciting events in GSC conversion [76,77]. Change to a stem-like phenotype from non-GSCs has been confirmed by assessing neurosphere and xenograft tumor formation, as well as cellular activity of classical GSC genes ( OCT4, NANOG, c-MYC , etc.)…”
Section: Molecular Mechanisms Of Glioma Stem Cell Resistance To Chmentioning
confidence: 99%
“…Change to a stem-like phenotype from non-GSCs has been confirmed by assessing neurosphere and xenograft tumor formation, as well as cellular activity of classical GSC genes ( OCT4, NANOG, c-MYC , etc.) [19,76,77]. Plasticity magnifies the ineffectiveness of current therapy, which not only spares GSCs but also replenishes those best suited to withstand subsequent therapy.…”
Section: Molecular Mechanisms Of Glioma Stem Cell Resistance To Chmentioning
confidence: 99%
“…Murine multipotent nestin-expressing stem cells, derived from either the hair follicle bulge area or dermal papilla possess sphere-forming capacity [8]. Our isolated multipotent nestin-positive cells also showed sphere-forming ability, which reflects self-renewing capacity [28], and was also found in the case of skin-derived neural crest stem cells [29] or skin-derived precursors [7]. Our isolated stem cells included the cells obtained from seven patients over 70 years of age (the oldest patient, 86 years old), and so our results indicate that skin-derived nestin-expressing follicle stem cells could be isolated even from patients over 70 years of age.…”
Section: Discussionmentioning
confidence: 99%